Single/reduced port surgery vs. conventional laparoscopic gastrectomy: systematic review and meta-analysis. Issue 4 (1st April 2022) - Alarcón, Isaias; Yang, Tao; Balla, Andrea; Morales-Conde, Salvador
Abstract: Introduction: The aim is to compare single port surgery (SPS)/reduced port surgery (RPS) versus conventional laparoscopy (CL) for gastrectomy for gastric cancer in terms of intra- and postoperative outcomes. Material and methods: After a search in Pubmed and Embase, six articles were included. Pooled analysis was used to evaluate the statistically significance for each variable. Results: Two hundred and thirty-three and 230 patients underwent SPS/RPS and CL, respectively. One hundred and eighty-eight patients and 45 patients underwent subtotal and total gastrectomy, respectively, using the SPS/RPS approach. One hundred and eighty-five patients and 45 patients underwent subtotal and total gastrectomy, respectively, by CL. In 85 patients, an extra trocar was systematically placed at the end of surgery. Statistically significant differences were not observed about preoperative staging. The pooled analysis regarding operative time, blood loss, postoperative complications, number of harvested lymph nodes and postoperative hospital stay showed that the only statistically significant difference between the two approaches is the shorter hospital stay in case of SPS/RPS. Conclusions: SPS/RPS total or subtotal gastrectomy shows a lower postoperative hospital stay, with comparable operative time, blood loss, early postoperative complication rate and number of harvested lymph nodes in comparison to CL, provided extensive experience in minimally invasive gastrectomy is present. Abbreviations: AGC: advanced gastric cancer; BMI: body mass index; CI: confidence interval; CL: conventional laparoscopy; LESS: laparoendoscopic single site; MD: mean difference; NOS: Newcastle-Ottawa Scale; OR: odds ratio; PRISMA: Preferred Reporting Items for Systematic Review and Meta-Analysis; ROBIN-I: Risk Of Bias In Non-randomised Studies – of Interventions; RPS: reduced port surgery; RR: risk ratio; SILS: single incision laparoscopic surgery; SPS: single port surgery; WMD: weighted mean differences